Embryogenesis Development of Pearl Catfish (Clarias gariepinus) The Fish Health and Environment Testing Laboratory of Muntilan - Sinuhaji, Etta Elis Dayanti; Usman, Zainal; Valentine, Riris Yuli (Jurnal Media Akuakultur Indonesia, 2024)
Pearl catfish (Clarias garipinus) is one of the freshwater fish from Indonesia which has a very important economic value and is much loved by the community. There is still very little information about embryonic development (embryogenesis). The purpose of this study was to determine the development of the embryo. The study was conducted on March 27 to May 25, 2023 at the Muntilan Fish Health and Environmental Testing Laboratory, Central Java. Observations were made on the spawning eggs of 1 male Pearl catfish and 1 female pearl catfish. The material was analyzed descriptively with the help of images of the developmental phases of each egg and information on the hatching time of the eggs. The results showed that the embryonic development of Pearl catfish includes the phase of Zygote cell division (clevage), 27 minutes from 22:22 to 22:45, morula Stage 2 hours from 22:45 to 00:45, blastula stage 1 hour and 21 minutes. 00:45 – 01:06, the gastrula stage lasts 4 hours 10 minutes 01:06 – 04: 00, The organogenesis stage to larval hatching 1,225 minutes or 20 hours 25 minutes from the initial stage. Hatchability of eggs in this study was 83.47%.